2016
DOI: 10.1038/nrclinonc.2016.128
|View full text |Cite
|
Sign up to set email alerts
|

Does the mobilization of circulating tumour cells during cancer therapy cause metastasis?

Abstract: Despite progressive improvements in the management of patients with locoregionally confined, advanced-stage solid tumours, distant metastasis remains a very common - and usually fatal - mode of failure after attempted curative treatment. Surgery and radiotherapy are the primary curative modalities for these patients, often combined with each other and/or with chemotherapy. Distant metastasis occurring after treatment can arise from previously undetected micrometastases or, alternatively, from persistent locore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
127
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(129 citation statements)
references
References 167 publications
2
127
0
Order By: Relevance
“…[16] summarizes the current knowledge on the effects of anti-cancer treatment on mobilization of CTCs into the circulation. It was shown that different types of treatment applied to cure locoregional disease (i.e., radiotherapy, surgery, systemic therapies) may actually contribute to the increase in the number of CTCs in patients' blood, or an increase in proliferative capacity of CTCs.…”
Section: Ctc Mobilization By Treatmentmentioning
confidence: 99%
“…[16] summarizes the current knowledge on the effects of anti-cancer treatment on mobilization of CTCs into the circulation. It was shown that different types of treatment applied to cure locoregional disease (i.e., radiotherapy, surgery, systemic therapies) may actually contribute to the increase in the number of CTCs in patients' blood, or an increase in proliferative capacity of CTCs.…”
Section: Ctc Mobilization By Treatmentmentioning
confidence: 99%
“…[12] Despite progressive improvements in the management of patients with locoregionally confined, advanced-stage solid tumors, distant metastasis remains a very common -and usually fatal -mode of failure after attempted curative treatment. [13] Surgery and radiotherapy are the primary curative modalities for these patients, often combined with each other and/or with chemotherapy. [13] Surgical interventions in patients with cancer, including biopsies, are commonly associated with increased concentrations of CTCs.…”
Section: Application Of Ctcs In Breast Cancer Diagnosismentioning
confidence: 99%
“…[13] Surgery and radiotherapy are the primary curative modalities for these patients, often combined with each other and/or with chemotherapy. [13] Surgical interventions in patients with cancer, including biopsies, are commonly associated with increased concentrations of CTCs. [13] High CTC numbers are associated with an unfavorable prognosis in many cancers.…”
Section: Application Of Ctcs In Breast Cancer Diagnosismentioning
confidence: 99%
“…Although IR showed positive therapeutic efficacy for many cancers, development of radioresistance, resulting in the tumor recurrence and metastasis involved multiple signaling pathways, remains a substantial clinical problem (5,6). The gene expressions affected by radiation therapy have been reported to be associated with anti-apoptosis, tumor aggressiveness, and enhanced metastatic potential such as resistance to hypoxia, invasiveness and motility, and epithelial-to-mesenchymal transition (EMT) (2). However, the critical regulator, which is involved in these processes and could be a potential target to circumvent radioresistance, has not been documented yet.…”
mentioning
confidence: 99%
“…The most types of radiation commonly used for cancer treatment include X-rays, gamma rays and charged particles. Ionizing radiation (IR) induces DNA damage, resulting in either cell-cycle arrest or apoptosis (1,2), to show antitumor activity, and is used alone or in combination with surgery, chemotherapy or immunotherapy to benefit cancer patients at different stages (3). For example, radiation therapy is used for breast cancer of earlier stage following breastconserving surgery.…”
mentioning
confidence: 99%